Phytochemical profiling and ameliorative effects of Achillea cretica L. on rat model of endometriosis. (23rd May 2020) - Bina, Fatemeh; Daglia, Maria; Santarcangelo, Cristina; Baeeri, Maryam; Abdollahi, Mohammad; Nabavi, Seyed Mohammad; Tabarrai, Malihe; Rahimi, Roja
Abstract: Ethnopharmacological relevance: Achillea cretica ( AC ) is a medicinal plant emphasized for treatment of gynecological disorders and pathological symptoms similar to endometriosis in traditional Persian medicine. Since information about its chemical constituents is limited, the aim of this study is to investigate phenolic composition of AC extract as well as its effect on experimental model of endometriosis. Materials and methods: RP-HPLC-PDA-ESI-MS/MS analysis was used for the determination of polyphenolic compounds. Endometriosis was induced in rats by suturing of uterus segments to abdominal wall of same rat, after eight weeks when the model was induced, it was followed by 28 days of treatment with 100, 200, and 400 mg/kg/day of hydroethanolic extract of the plant. Blood samples and implanted tissues were collected in the final day, and area of foci, tumor necrosis factor-α, vascular endothelial growth factor, interleukin-6, and serum total thiol molecules were measured and compared with positive group (0.2 mg/kg/day letrozole) and control group (solvent of extract: normal saline). Implanted tissue sections of the sacrificed rats were also assessed histopathologically. Results: Nine polyphenolic compounds were identified in AC extract including 7 flavonoids and 2 phenolic acids. Plant extract decreased area of foci and cytokine levels in serum and local tissue. Histopathological assessments confirmed the effectiveness of treatments by decreasing the thickness of epithelial layer and increasing the infiltration of leukocytes into this layer. Doses of 100 mg/kg and 400 mg/kg of extract showed better effects in comparison with the dose of 200 mg/kg in reduction of cytokine levels and size of implanted tissue. Extract and letrozole did not demonstrate significant effect on thiol level. Conclusion: AC aerial extract may be a favorable medicine for management of endometriosis by modulating inflammatory cytokines; however, further studies are needed for more conclusive and reliable decision about its efficacy and safety. Graphical abstract: Image 1